2005
DOI: 10.1080/08916930400022947
|View full text |Cite
|
Sign up to set email alerts
|

Anti-scl-70

Abstract: Evidence-based guidelines suggest that anti-Scl-70 antibodies are very useful in the diagnosis and clinical management of SSc patients and also to establish prognosis in these patients, particularly those with diffuse skin involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 3 publications
3
26
0
4
Order By: Relevance
“…ATA is found in about 20% of SSc patients with high disease specificity (97-100% vs healthy controls and other CTDs by immunodiffusion), in about 37% of patients with dcSSc, and in less than 10% of patients with lcSSc [27]. A recent study by Mahler et al [28] confirmed the high specificity of ATA, especially at high titers, determining a prevalence in systemic lupus erythematosus (SLE) of less than 5%.…”
Section: Autoantibodies In Sclerodermamentioning
confidence: 83%
“…ATA is found in about 20% of SSc patients with high disease specificity (97-100% vs healthy controls and other CTDs by immunodiffusion), in about 37% of patients with dcSSc, and in less than 10% of patients with lcSSc [27]. A recent study by Mahler et al [28] confirmed the high specificity of ATA, especially at high titers, determining a prevalence in systemic lupus erythematosus (SLE) of less than 5%.…”
Section: Autoantibodies In Sclerodermamentioning
confidence: 83%
“…Worsening of prognosis is associated with persistent levels of antibodies [11]. Immunodiffusion, immunoblot, immunoprecipitation, and ELISA assays (with natural or recombinant antigen) are used to detect anti-Scl 70 antibodies [12][13][14][15]. Using a recombinant peptide as antigen has allowed better standardization with consistent results between different laboratories [16].…”
Section: Discussionmentioning
confidence: 99%
“…рисунок, б). ДС АТА для ССД высока (97-100%) при срав-нении со здоровым контролем и с пациентами с другими системными воспалительными РЗ при использовании ме-тода ДИД [53]. Специфичность зависит от метода и снижа-ется при использовании ИФА.…”
Section: таблицаunclassified